Penetapan Harga Berbasis Penerimaan Konsumen di Dual-Channel Supply Chain - Widodo, Erwin (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
Dual-Channel Supply Chain (DCSC) is a mixed structure which simultaneously utilizes both offline and online channel to distribute one particular product or service. This structure provides market reach extension in which eventually leads to revenue increase. Whatsoever, aside of this advantage, DCSC also brings some challenging problems. One prominent problem is of about between-channel pricing-problem. In its practice, DCSC actors often apply intuitive offline and online pricing without further analytical evaluation. Yet there is no representative mechanism to address this critical problem. This paper attempts to resolute this challenge by proposing a qualitative estimation mechanism on customer acceptance on online channel relative to offline one. This proposed approach is about to utilize an interplay relationship between offline and online prices. The main parameter to consider is a ratio of customer acceptance parameters. These parameters are elicited from 3 groups of products which are sold under DCSC structure in Indonesian cases to exhibit the different properties in each product group. Numerical experiment result shows that the utilization of this pricing mechanism may increase the financial performance of DCSC under observation.